Mengembangkan Sikap Positif dan Pemahaman Siswa Melalui Pembelajaran Kontekstual dengan Metode Demonstrasi atau Field Trip: Developing Positive Attitudes and Student Understanding Through Contextual Learning with Demonstration Methods or Field Trip - Andriansyah, Eka Hendi (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is to create the formation of students' attitudes and understanding of teaching materials through a contextual approach by comparing the use of two methods that are almost the same, namely the demonstration method and the field trip method. The contextual approach is very compatible with the 2013 curriculum, in which students are required to be able to construct their learning through an approach by leading to real-world learning. The research method used is the experimental method that tests the use of two learning methods that exist in contextual learning, namely the control class treatment with the Demonstration method and the experimental class treatment with the field trip method. It was found the significance of the differences in learning by using a contextual approach, especially using the field trip method compared to using a contextual approach with a demonstration method. Learning done with field trips results in higher scores in terms of understanding as well as student attitudes compared to demonstration methods on the same contextual approach. Bringing students directly into the real world while providing students the opportunity to socialize with the world around them and learn to interact in the right way so that they can create better attitudes than learning in the classroom.